FOURCE: Terminal year-end report: - Chen, Cathrena Nicole Huang (Animo Repository, 2021)
FOURCE is a corporation founded by four university students who aim to bring positive change to the world. It all started with an innovative product idea, a multifunctional device that was created to help the vulnerable protect themselves from street danger. Admittedly, the entrepreneurs had to shift the focus of the product’s purpose to protection from domestic danger and an emergency tool for power outages. This is due to the fact that the business has been operating at a time of great uncertainty. Like any other business, FOURCE had to deviate from the original plan to cater to the evolving needs and concerns of the consumers during the pandemic. Because of this, the company chose to adapt and shift its operations online. Fortunately, the entrepreneurs were able to carry out the business’ mission and achieve the company objectives through effective digital marketing strategies and awareness campaigns. This is a result of the continuous effort of the team to understand the needs of the target market in order to fulfill, and even exceed their expectations.